Agenda Setting and Impact of Local Media in Shaping Public Agenda – Case Study - Višnovský, Ján; Baláž, Martin (Communication Today, 2025)
The study deals with issues of agenda setting and influence of media operating at the local level to serve the public agenda in both theoretical and empirical perspective. The focus is on media, political and public agenda as well as the development of ideas about them. The main goal of the authors was to test hypotheses regarding the ability of media in agenda setting and highlighting certain attributes that influence their interpretation in terms of the public, as well as whether these effects manifest themselves at the local level. As an example, the authors studied the city of Žiar nad Hronom, Slovak Republic, which is also the publisher of the weekly Mestské noviny. They were interested in the function of the local media, especially the periodical, in the process of agenda setting, and their ability to influence public opinion in specific areas. These referred mainly to current and attractive themes form the viewpoint of the public and politicians. Locally, regional media is an essential tool for political communication and public opinion formation in a geographically defined area, and this markedly affects the character of the public agenda in the area in which they operate. Therefore, the authors were more interested in the impacts on the functioning of the media and media production at the local level.